2016
DOI: 10.1039/c5py01344e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of polyacrylonitrile hollow fiber membranes from ionic liquid solutions

Abstract: PAN hollow fiber membranes with good pore morphology have been fabricated using solvent mixtures of ionic liquids and DMSO, which has a lower toxicity than other commonly used polar organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…The Gibbs free energy of mixing (ΔG m ) is an informative parameter to predict the homogeneity of a polymer/solvent mixture [21]. In particular, if ΔG m is negative, the polymer is expected to completely dissolve in the solvent.…”
Section: Estimation Of Gibbs Free Energy Of Mixingmentioning
confidence: 99%
“…The Gibbs free energy of mixing (ΔG m ) is an informative parameter to predict the homogeneity of a polymer/solvent mixture [21]. In particular, if ΔG m is negative, the polymer is expected to completely dissolve in the solvent.…”
Section: Estimation Of Gibbs Free Energy Of Mixingmentioning
confidence: 99%
“…In a typical procedure, 2 g of graphite flakes were mixed into a round-bottomed flask containing 250 ml of H 2 SO 4 and the resulting mixture was stirred for 1 hr at 25 °C. About 10 g of KMnO 4 were added to the mixture under stirring until a viscous dark-green mixture was obtained and stirring was continued for 24 h at 25 °C. The mixture was transferred into an ice bath and a mixture containing 100 ml of H 2 O 2 and 500 ml of deionized (DI) water was added slowly.…”
Section: Graphene Oxide (Go) Synthesismentioning
confidence: 99%
“…We prepared flat sheet cellulose membranes by dissolving in 1-ethyl-3-methylimidazolium acetate ([EMIM]OAc) [1], hollow fiber membranes of polyacrylonitrile from solution in dimethyl sulfoxide/([EMIM]OAc [4] and of cellulose acetate in acetone/([EMIM]OAc [3], and hydroxyl-polytriazole in dimethyl carbonate/[EMIM]OAc [7]. PES is one of the most common membrane materials in the membrane industry for ultrafiltration and as support for reverse osmosis [8] with application in desalination, waste water treatment, biotechnology and pharmaceutical industries, oil-water separation, protein mixture separation, food industry and other filtration processes.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids are environmentally friendly solvents that result in membranes with excellent performance characteristics. Kim et al . found that the use of [EMIM]DEP as solvent resulted in PES membranes with a smaller molecular weight cut‐off (MWCO) and higher permeability than NMP, DMF, and DMA.…”
Section: Introductionmentioning
confidence: 99%